Avaliação comparativa das alterações temporais da decomposição da cartilagem auricular de bovinos, suínos e coelhos, submetida à exumação para estimativa do intervalo post mortem (IPM) - Leonardo Lima Gorza (2021)
Estimation of postmortem interval (PMI) is a challenge, especially when the interval between cadaver examination and death occurs after several weeks to months. The analysis of tissues more resistant to putrefaction, such as cartilage, can be used in advanced PMI. The aim of this work was evaluates and compares macroscopic and microscopic changes of the rabbits, cattle and pigs auricular cartilage, after exhumation in different PMI. Eight pairs of ears/ species were used. Eight samples were obtained from the ears of each rabbit, corresponding to PMI 0, 5, 10, 15, 20, 25, 30 and 150 days. From the cattle and pig ears, were obtained twelve samples corresponding to PMI 0, 5, 10, 15, 20, 25, 30, 35, 40, 50, 60 and 150 days. The samples were buried in graves, being opened only at each PMI, except the 150-day grave, that was periodically opened to analyze the total sample decomposition. The sandy clay-soil showed an average temperature, humidity and pH of 23.5º C, 54.9% and 7.0, respectively. The temperature and humidity air average values were 23.2º C and 52.3%, respectively. The average of rabbit’s samples hair loss was significantly higher in the five days and statistically similar to the pig samples at 30 days. At 60 days, the averages of hair loss were similar between cattle and pig samples. The rabbit ear samples mass loss was always greater in regard to the average of cattle and pig samples. At 60 days, cattle and pig ear samples mass loss averages were statistically similar. The loss of sample area was statistically similar in all species in most PMI. At 150 days, all cattle samples had decomposed completely, unlike rabbit and pig samples. Microscopic analysis, regarding to cartilage stain, loss of chondrocyte nuclear material and tissue architecture, showed gradual increase of these postmortem changes through PMI, regardless of animal species, although the percentage of samples with these changes have been varied between the three species within each PMI. Fungi and bacterial colonization were earlier in the cattle and pig samples, although it also has varied between species within each PMI. Significant thinning of cartilage thickness was observed over time in all species. Correlation between the time and the sample weight loss or the cartilage thickness was strong, being these variables adequate for estimation of the PMI. It is concluded that the auricular cartilage postmortem examination can be used for determining PMI, that there are differences between species regarding gross and microscopic postmortem changes, and despite the mass loss of rabbit ear samples is higher compared with cattle and pig samples until 30 days, the total sample decomposition occurs first in cattle, followed by rabbit and pig samples.